Temozolomide therapy for aggressive functioning pituitary adenomas refractory to surgery and radiation: a case series. Issue 1 (26th May 2017) - Jordan, Justin T; Miller, Julie J; Cushing, Tucker; Seijo, Marlon; Batchelor, Tracy T; Arrillaga-Romany, Isabel C; Shih, Helen A; Nachtigall, Lisa B; Loeffler, Jay S; Dietrich, Jorg
Abstract: Background: Treatment of aggressive pituitary adenomas typically involves a multimodality approach based on histopathological features and may include pharmacotherapy, surgery, and occasionally radiation therapy. In cases of treatment-refractory tumor progression, chemotherapy may be considered; however, no standard chemotherapeutic regimen has been established. Literature review suggests that temozolomide may have a beneficial role in a subset of cases. To understand the efficacy of temozolomide in progressive pituitary tumors, we reviewed the outcomes of cases at our center. Methods: We performed a retrospective chart review to report the outcome and unique features of 7 patients with aggressive functioning pituitary adenomas or carcinomas treated with temozolomide. Tumor pathology included somatotroph (n = 1), corticotroph (n = 3), and lactotroph (n = 3) tumors. Results: Four of the 7 patients had at least 2 prior resections, and all had prior radiation and surgery before treatment with temozolomide. Notably, all patients showed response to therapy, defined as either stable disease (43%) or partial response (57%). Median progression-free survival was 1.66 years, and median overall survival was 4 years. Conclusion: Our data suggest that temozolomide has an important role in the management of aggressive functioning pituitary tumors that are resistant to standard therapies, and that optimization of therapy with temozolomide may involve individualized regimens. Future prospective clinical trials should be considered.